Forestry Sector and Policies on Sustainable Development in Vietnam: Analyze from the Input - Output Model - Hung, Duong Manh; Trinh, Bui (International Journal of Social and Administrative Sciences, 2019)
Deforestation in Vietnam is among the most serious in the world, with many causes but the main reason is not seeing the importance of the forestry sector. Authorities seem to be "crazy loving" the GDP indicator, so it seems that everything is compared to GDP; If the ratio of a certain industry in GDP is low, it seems that the industry is not important enough! This study tries an attempt to estimate distribution of forestry to economy and environmental. This study uses an input - output system to highlight the importance of the forestry sector not only to the environment but also to the economy. The results from this analysis show that about 90% of the forest products are used for intermediate consumptions (for production) and only 10% for final uses, especially timber products. The imported value of the forest sector accounted for 43.76%, implying a need to change the plantation structure to increase the high value of timber from long rotation plantation forest to meet domestic and export demands. Researching also shows that in order to increase the value of timber exports, particular attention should be paid to the structure of the plantation forest towards converting to long rotation plantation forest. In term of environmet, the results show the role of afforestation in reducing emission. Moreover, the production of timber and wood processing sector also stimulates the planting and tending sector. Therefore, encouraging these sectors will spill over reducing emission.